2017
DOI: 10.1371/journal.pone.0178119
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of rocket salad under pre-harvest and postharvest stresses: A transcriptomic resource for Diplotaxis tenuifolia

Abstract: Diplotaxis tenuifolia L. is of important economic value in the fresh-cut industry for its nutraceutical and sensorial properties. However, information on the molecular mechanisms conferring tolerance of harvested leaves to pre- and postharvest stresses during processing and shelf-life have never been investigated. Here, we provide the first transcriptomic resource of rocket by de novo RNA sequencing assembly, functional annotation and stress-induced expression analysis of 33874 transcripts. Transcriptomic chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 69 publications
5
21
0
Order By: Relevance
“…Changes in gene expression were detected both during the 24 h stress period in response to the stress treatments, and also persisted after seven days of post-harvest storage. Transcriptomic data indicated that DtTMT was upregulated by all three stresses after 24 h [19,40]. Data here are in agreement but also indicate that the upregulation occurs much earlier, after only 2 to 6 h in the three stresses imposed as compared with the unstressed control.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Changes in gene expression were detected both during the 24 h stress period in response to the stress treatments, and also persisted after seven days of post-harvest storage. Transcriptomic data indicated that DtTMT was upregulated by all three stresses after 24 h [19,40]. Data here are in agreement but also indicate that the upregulation occurs much earlier, after only 2 to 6 h in the three stresses imposed as compared with the unstressed control.…”
Section: Discussionsupporting
confidence: 84%
“…Glucosinolates are significantly reduced in rocket leaves after one or two weeks of storage at 4 • C [18]. However, transcriptomic analysis showed that DtTMT expression was upregulated by wounding, as well as cold and ambient dark stresses applied to leaves of Diplotaxis tenuifolia for 24 h following harvest [19]. This presumably increases the breakdown of glucosinolates into isothiocyanates on consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant senescence is affected by respiratory metabolism, which provides the energy for a range of biochemical processes [9]. In leafy crops such as salads, pre-harvest and post-harvest stresses (even of short duration) contribute to changes in metabolism that accelerate quality losses [10]. The major symptoms of post-harvest senescence of Zizania latifolia are shell etiolation, surface browning, transpiration, respiratory disorders, and tissue hollowness [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dark-induced senescence is well characterized by the loss of chlorophyll and proteins, by enhanced ROS production, or by increased lipid peroxidation and membrane permeability. Changes in phytohormones, such as the induction of ethylene (ET) emission and the drop in the content of cytokinins (CKs), are also important regulators of this process, since these two hormones function as the main controllers of senescence (Luschin-Ebengreuth and Zechmann 2016, Cavaiuolo et al 2017). From this aspect, the role of antioxidant enzymes in controlling ROS accumulation is particularly important in darkinduced senescence.…”
Section: Dark-induced Senescencementioning
confidence: 99%